Nihil novi sub sole: law from the perspective of political accelerationism - Dudek , Michał (Hybris, 2018)
This article focuses on political accelerationism—an idea that proposes to use capitalism against itself either by making it as a whole go even faster, pushing it to its limits and beyond until it collapses, or by appropriating some of its elements or tendencies for alternative, emancipatory purposes. It analyses two significant versions of this idea—that of Benjamin Noys and that of Nick Srnicek and Alex Williams—from the perspective of the following question: Is political accelerationism similar to certain previous developments in left critical thought in that it offers a new approach to law or, if it does not contain any explicitly expressed original take on law, enables a novel and fresh conceptualisation of law to be drawn from it? The article concludes that so far political accelerationism does not offer an original approach to law and that any perspectives on law that can be drawn from this idea are reminiscent of basic Marxist approaches to law.